PROCESSING PLATE-PLATE IMMOBILIZATION DATA OF NANOCELLULOSE FURNISHES - Dimić-Misić, Katarina; Nieminen, Kaarlo; Sixta, Herbert; Paltakari, Jouni; Maloney, Thaddeus (Journal of Applied Engineering Science, 2014)
Appropriate regularization algorithm is proposed for choosing the regularization parameter based on nosy immobilization viscosity data. Complex fluids as nanocelluose based high consistency suspensions have very complex rheological behavior. This paper describes Tikhonov regularization procedure for reducing the noise from immobilization rheograms of nanocellulose based furnishes, performed on immobilization cell at MCR 300 rheometer. Noise observed in immobilization rheograms can make evaluation of data very complicated and lead to wrong interpretation of rheological behavior observed. They are related to the change of consistency accompanied with rearrangement of the particles during shear induced dewatering accompanied with wall slip and boundary effects typical for gel like nanocellulose suspensions. Hereby we propose a model with regularization parameters suitable for applying to parallel disk data for flocculated gel like high consistency suspensions while consistency increasing mode upon shearing .